HUBUNGAN STATUS INSTABILITAS MIKROSATELIT DAN EKSPRESI P53 DENGAN ETIOPATOLOGI ADENOKARSINOMA KOLOREKTAL PADA ORANG INDONESIA DI KELOMPOK USIA KURANG DARI 40 TAHUN - Kiki Lukman; Brigitta M. Dewayani; Bethy S. Hernowo; Basrul Hanafi; Tri Hanggono Achmad; Suwandi Sugandi (Indonesian Journal of Applied Sciences, 2012)
Epidemiologically, the percentage of colorectal adenocarcinoma (CRC) in the age group ≤40 years old in Indonesia is higher than in the West European, North American and other developed Asian countries with different clinico-pathological features. In the afromentioned countries, the carcinogenesis pathway of this group is hereditary which show high microsatellite instability (MSI), whereas the age group >40 years old is sporadic of which show chromosomal instability (CIN) with the mutation of p53 gene. To elucidate the carcinogenesis pathway with its molecular characteristics of this group among Indonesians, a cross sectional study was conducted by performing the immunohistochemical detection of MLH1 and MSH2 expression (MSI status), and mutated p53 gene expression (CIN) in the CRC group ≤40 years old and >40 years old at Dr. Hasan Sadikin Hospital, Bandung, from May 2008 until November 2009. Thirty nine CRC patients, consisting of 22 patients of  ≤40 years old and 17patients >40 years old, were eligible for this study. The CRC patients of ≤40 years old showed 4 MSI high,  1 MSI lowand 17 MSS (microsatellite stable), associated with 10 p53 positive and 12 p53 negative status. In the CRC group of >40 years old, there was no MSI high, but 4 MSI low and 13 MSS were found, associated with 11 p53positive and 6 p53negative status. There was no significant difference with regards to the association between MSI status and p53 expression in both groups (p MSI=0.95, p p53=0.23).